IDENTIFIKASI TELUR CACING ASCARIS LUMBRICOIDES PADA KEMBANG KOL (BRASSICA OLERACEA VAR. BOTRYTIS) DENGAN METODE SEDIMENTASI - Choirudin, Nadia Pramesthy Choirudin; Sasongkowati, Retno; Astuti, Sri Sulami Endah (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: Ascaris lumbricoides is the causative agent of a helminthic diseases known as ascariasis. According to the World Health Organization (WHO), helminthic diseases constitute more than half of the health issues in developing countries. It is caused by poor sanitation and a tropical climate that supports the development of worms. Transmission of worm eggs to humans can be through vegetables that grow near the ground, one of them is cauliflower. Objectives: The study aimed to identify the presence of Ascaris lumbricoides eggs in cauliflower sold at Krembung Market, Sidoarjo Regency. Materials and Methods: The method used is sedimentation using 0,2% NaOH reagent with the principle of centrifugal force which results in the separation of worm eggs and supernatant. This method can precipitate eggs without damaging them, making it easier to identify the type of worm eggs. Results: The research was carried out in April 2023 and the results showed that from the 12 samples sold on mats, there were 2 samples (17%) contaminated with infertile Ascaris lumbricoides eggs. Meanwhile, from 12 samples sold on table, no Ascaris lumbricoides eggs (0%) were found. Conclusions: Based on the research results, Ascaris lumbricoides eggs were found in 2 out of 12 samples of cauliflower sold on mats.